STRATEGI DAN TANTANGAN KONVERGENSI MEDIA DALAM KOMUNIKASI PENYIARAN DIGITAL - Swani, Ni Made; Widaswara, Rieka Yulita; Sutama, I Wayan (IAHN Gde Pudja Mataram, 2024)
The leap of digital technology has brought significant changes in broadcast communication. The dynamics of these changes have significant consequences for media convergence, especially in the management of the Hindu pulpit program at TVRI NTB. Using a case study approach, this article seeks to describe the strategies and challenges of media convergence in the Hindu pulpit program through the YouTube channel. The results showed that the current challenges of media convergence include the amount of content that must be uploaded, the lack of human resources who handle content management, the less interesting pulpit program, and the absence of sufficient time to watch the pulpit program. Strategies used to deal with media convergence by conducting various promotions through other media, broadcasting special events and creating interesting and relevant topics.